Evaluation of Net Energy Obtainable from Combustion of Stabilised Olive Mill By-Products - Antonio Messineo; Francesco Asdrubali; Roberto Volpe (Energies, 2012)
This work is aimed at calculating the energy content of the residues from olive oil production. Olive pulp, olive husk and sludge (a mixture of olive pulp and husk) have been analyzed separately. Olive Mill Effluents (OME) are normally a problem for olive mill farms, yet they may be used as feedstock for biomass-fuelled power plants. Nonetheless, OMEs are characterized by a relatively high humidity content and are produced only during the olive season. Thus, OME need a stabilization process to be employed as a solid biofuel throughout the year. The analyses conducted attempt an evaluation of the energy consumption of a three-stage stabilization process: drying, milling and pelletising. The net electrical energy available from OME is then calculated as a difference between gross energy available and energy consumed for stabilization. The gross available electrical energy was calculated based on direct energy conversion of the stabilized feedstock on a small scale direct combustion and Organic Rankine Cycle (ORC) turbine. Results show that OME are suitable for energy production. Approximately 4500 kJ/kg of net electrical energy may be obtained out of olive sludge or olive pulp, while olive husk shows a potential gross energy of 3400 kJ/kg.